2020
DOI: 10.1080/17515831.2020.1720380
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on tribology and microhardness of laser synthesized Ti-Al2O3/Zn coatings on Ti-6Al-4V alloy

Abstract: The study of laser cladding of 90Ti-10Al 2 O 3 , 90Ti-8Al 2 O 3 -2Zn and 90Ti-4Al 2 O 3 -6Zn coatings onto Ti-6Al-4V alloy, with intention to produce defect-less, high microhardness and wear resistant coating was carried out. The coatings were deposited onto Ti-6Al-4V alloy at 900 W laser power and 0.6 m/min laser scan speed. Microstructures and phase constituents of the developed coatings were investigated by using a scanning electron microscope (SEM) and Xray diffractometer correspondingly. Vickers microhard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The average friction coefficients of the Ni60/WC coatings exhibit a progressive trend, measuring 0.56, 0.52, 0.43, and 0.5 as the scanning speed increases from 8 mm/s to 14 mm/s. Mthisi et al [37,38] prepared different composite coatings on the substrate with friction coefficients ranging from 0.6-0.76; the results of this paper are similar to theirs and have lower coating friction coefficients. This pattern demonstrates an initial decrease followed by an increase in friction coefficients with the rising scanning speed, which aligns with the observed variations in microhardness.…”
Section: Friction and Wear Performancesupporting
confidence: 71%
“…The average friction coefficients of the Ni60/WC coatings exhibit a progressive trend, measuring 0.56, 0.52, 0.43, and 0.5 as the scanning speed increases from 8 mm/s to 14 mm/s. Mthisi et al [37,38] prepared different composite coatings on the substrate with friction coefficients ranging from 0.6-0.76; the results of this paper are similar to theirs and have lower coating friction coefficients. This pattern demonstrates an initial decrease followed by an increase in friction coefficients with the rising scanning speed, which aligns with the observed variations in microhardness.…”
Section: Friction and Wear Performancesupporting
confidence: 71%
“…However, some micropores are visible in the coating (as shown in Figure 4(a–c)). It might be due to the inclusion of the gases during the cladding process [19-21]. Apart from the micropores, no other types of defects are observed in the coating-substrate interfaces and the clad portion.…”
Section: Resultsmentioning
confidence: 99%
“…Their investigation revealed an increase in hardness up to 4.5 times and wears resistance 3 times. Mthisi et al [13] used Ti, Al 2 O 3 and Zn powders for creating a high hardness and wear-resistant coating on titanium alloy using 900 W laser sources. The authors concluded that by increasing the Zn content, defects were mitigated, but the hardness and wear-resistant ability of the coating was decreased.…”
Section: Introductionmentioning
confidence: 99%